Alcohol Consumption in Diabetic Patients with Nonalcoholic Fatty Liver Disease - Preya J. Patel; David Smith; Jason P. Connor; Leigh U. Horsfall; Kelly L. Hayward; Fabrina Hossain; Suzanne Williams; Tracey Johnson; Katherine A. Stuart; Nigel N. Brown; Nivene Saad; Andrew D. Clouston; et al. (Canadian Journal of Gastroenterology and Hepatology, 2017)
Aim. To examine the association between lifetime alcohol consumption and significant liver disease in type 2 diabetic patients with NAFLD. Methods. A cross-sectional study assessing 151 patients with NAFLD at risk of clinically significant liver disease. NAFLD fibrosis severity was classified by transient elastography; liver stiffness measurements ≥8.2 kPa defined significant fibrosis. Lifetime drinking history classified patients into nondrinkers, light drinkers (always ≤20 g/day), and moderate drinkers (any period with intake >20 g/day). Result. Compared with lifetime nondrinkers, light and moderate drinkers were more likely to be male (p=0.008) and to be Caucasian (p=0.007) and to have a history of cigarette smoking (p=0.000), obstructive sleep apnea (p=0.003), and self-reported depression (p=0.003). Moderate drinkers required ≥3 hypoglycemic agents to maintain diabetic control (p=0.041) and fibrate medication to lower blood triglyceride levels (p=0.044). Compared to lifetime nondrinkers, light drinkers had 1.79 (95% CI: 0.67–4.82; p=0.247) and moderate drinkers had 0.91 (95% CI: 0.27–3.10; p=0.881) times the odds of having liver stiffness measurements ≥8.2 kPa (adjusted for age, gender, and body mass index). Conclusions. In diabetic patients with NAFLD, light or moderate lifetime alcohol consumption was not significantly associated with liver fibrosis. The impact of lifetime alcohol intake on fibrosis progression and diabetic comorbidities, in particular obstructive sleep apnea and hypertriglyceridemia, requires further investigation.